Strategic Planing to Develop Good Dairy Farming Practices in Smallholder Dairy Farms in Batu City, East Java - Reni Indarwati; Herawati Herawati; Endang Arisoesilaningsih (Indonesian Journal of Environment and Sustainable Development, 2015)
Some of the objectives to be achieved in this research is to describe the attack profile of subclinical mastitis on Etawah Crossbreed Goats (ECG) in some smallholder farms, to identify risk factors that contribute to subclinical mastitis attacks and to compile a strategic plan to develop Good Dairy Farming Parctices (GDFP) in Batu. The data were gathered by interviewing smallholder farmer and direct observation in the three farms goats in Batu (Bumiaji, Pesanggrahan, Temas  and Beji village). California Mastitis Test (CMT) is used to detect subclinical mastitis on 51 ECG lactation belonging to farmer. Risk factors Identification of subclinical mastitis conducted by Spearman correlation analysis. All of smallholder compared with GDFP concept using gap analysis. Meanwhile, the strategic development plan of GDFP in Batu was done by the Root Caused analysis. The results showed that 100% subclinical mastitis attacks occurred on three dairy goats farms in Batu City  with the level 31-80% percentage of attacks. This subclinical mastitis attacks positively correlated with milk production (p <0.01). The risk factors of subclinical mastitis partly because of the environment (p<0.01), milking procedure (p <0.01) and health management (p <0.01) were not right. The strategic plan to develop GDFP in Batu City are Increase knowledge and awareness of farmers about how to implement good dairy farming practices on Etawah Crossbreed farm, particularly in the benefits of clean environmental, handling and using goat manure, the benefits of sanitation and disinfection of udder, the effect of milking frequency on udder health and the urgency of separation between healthy and sick goats. Keywords:  Good dairy farming practices, risk factors, subclinical mastitis